2014
DOI: 10.1517/13543784.2014.892924
|View full text |Cite
|
Sign up to set email alerts
|

The clinical development of p53-reactivating drugs in sarcomas – charting future therapeutic approaches and understanding the clinical molecular toxicology of Nutlins

Abstract: Medicinal chemistry strategies, based on structure-based drug design, are required to re-engineer cis-imidazoline Nutlin HDM2-binding antagonists into less haematologically toxic drugs. In silico modelling is also required to predict toxicities of other p53-RA drugs at a much earlier stage in drug development. Whether p53-RA drugs will be therapeutically effective as a monotherapy remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 115 publications
0
8
0
Order By: Relevance
“…As ‘specific’ MDM2 inhibitors in the clinic have shown strong adverse effects 16 , we determined whether specific targeting of MDMX could serve as an alternative for MDM2 inhibitor-based therapies in UMs, especially in combination with Sotrastaurin. Therefore, we created OMM2.3- and MEL202-derived cell lines containing two distinct MDMX-targeting short hairpin RNAs (shRNAs; i-shMDMX) or control shRNA (i-shCtrl) under control of a doxycycline-inducible promoter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As ‘specific’ MDM2 inhibitors in the clinic have shown strong adverse effects 16 , we determined whether specific targeting of MDMX could serve as an alternative for MDM2 inhibitor-based therapies in UMs, especially in combination with Sotrastaurin. Therefore, we created OMM2.3- and MEL202-derived cell lines containing two distinct MDMX-targeting short hairpin RNAs (shRNAs; i-shMDMX) or control shRNA (i-shCtrl) under control of a doxycycline-inducible promoter.…”
Section: Resultsmentioning
confidence: 99%
“…It could suggest that only inhibiting the MDM2–p53 interaction might not be sufficient to fully unleash p53 and achieve a synergistic response, at least in vitro. Even so, functional MDM2 inhibition might not be the optimal way to go in patients, due to the previous reported adverse effects 16 , 20 , 21 . Therefore, we focused our studies on targeting MDMX, because mouse studies have indicated that depletion of MDMX has much less detrimental effects on the well-being of the organism, most likely because MDMX is less universal expressed in adult tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Nutlins have shown preclinical activity in malignancies with elevated MDM2 or MDM4 expression such as sarcomas, neuroblastomas and some leukemias, including CLL. [18][19][20][21][22][23] Despite these promising initial results, the limited potency and bioavailability of these compounds restrict their clinical use. In addition, the issue of sparing non-tumor tissue from unwanted p53 accumulation and apoptosis remains unresolved.…”
Section: The P53 Pathway As a Therapeutic Targetmentioning
confidence: 99%
“…Augmentation of this signaling pathway occurs in over 50% of malignancies and is caused either by suppression of p53 activity via MDM2 ± MDM4 amplification in p53 wild‐type alleles or by p53 mutational events that result in loss of p53 tumor suppression. Numerous therapeutic strategies targeting aberrant p53 signaling are being developed, including MDM2 inhibitors in wild type p53 tumors, dual HDM2/HDMX antagonists, p53‐binding antagonists, and agents that restore the activity of mutant p53 . Altered p53 signaling is evident in sarcomagenesis , and these therapeutic strategies have great potential in the treatment in a variety of STS subtypes, especially in chemoresistant tumors.…”
Section: Targeting Cell Cyclementioning
confidence: 99%